Peningkatan Pemahaman Penjumlahan dan Pengurangan Bersusun melalui Media Pajar Jurang - Febrianti, Nabilla Eka; Istianah, Farida (CV. Kurnia Grup, 2025)
Mathematics learning in lower grades still faces various challenges, particularly in column addition and subtraction, as many students have not yet fully understood place value concepts. This study aimed to examine the effect of using the Pajar Jurang learning media on second-grade students’ understanding of column arithmetic operations. This research employed a quantitative approach with a one-group pretest–posttest design and was conducted in a second-grade elementary school classroom. The research subjects consisted of 15 students, and the entire population was used as the sample through a census technique. Data were collected using learning achievement tests administered before and after the implementation of the Pajar Jurang media. Data analysis involved calculating learning mastery percentages, N-Gain scores, and conducting a paired sample t-test. The results showed a significant improvement in students’ understanding, indicated by an increase in learning mastery for subtraction from 46.67% to 93.33% and for addition from 40% to 86.67%. The N-Gain values fell within the moderate to high categories, and the t-test results revealed a significant difference between pretest and posttest scores. These findings indicate that the Pajar Jurang media is effective in improving students’ understanding of column arithmetic operations and has strong potential for use in lower-grade mathematics instruction.